Pengembangan Media Diorama Keragaman Budayaku Pembelajaran IPAS Materi Keragaman Budaya dan Kearifan Lokal Kelas IV SD Negeri 1 Gedong Kabupaten Kendal - Putri, Safira Amalia; Tyas, Dewi Nilam (Jurnal Simki Pedagogia, 2026)
This study aims to develop a diorama media "My Cultural Diversity" for science learning on cultural diversity and local wisdom, to test its feasibility and effectiveness for science learning on cultural diversity and local wisdom, in improving the learning outcomes of fourth grade students. This R&D research with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) uses descriptive statistical analysis techniques on potential and problem data, expert opinions, teachers and students collected with interview sheets and questionnaires. The parametric inferential statistical analysis is used to test changes in student learning outcomes collected using pretest-posttest question instruments. The trial was conducted on a small scale (7 students) and a large scale (20 students). The results of the media validation are very suitable for use, reaching a score of 98% (material experts) and 93% (media experts). Based on the results of the paired sample t test, the t value = -16.606 with a p-value = 0.000. The significance value indicates a significant difference between learning outcomes before and after media use, supported by N-Gain values ​​of 0.451 and 0.433, respectively (moderate category). Thus, the "My Cultural Diversity" diorama demonstrates effectiveness in student learning outcomes in the subject of cultural diversity in science.